Kajian Ekranisasi Penokohan Dalam Novel Karya Ima Madaniah Dan Film Yang Disutradarakan Oleh Findo Purwono Dengan Judul Assalamualaikum Calon Imam (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Ecranization as a process off white sailing or the transfer of a novel into a film that results in changes, such as words that turn into action or real images. The purpose of this research is to analyze novels and films in terms of characterization, namely the main character in the novel Assalamualaikum Calon Imam by Ima Madaniah and the film Assalamualaikum Calon Imam by director Findo Purnomo. The transfer of the novel into a film as a form of appreciation for the novel so that the film entitled Asssalamualaikum Calon Imam can be enjoyed by FTV fans and broaden their horizons. Research that uses an objective approach. The source of data in this study is an analysis of novels and films. One of the techniques in collecting data in this study is by using data analysis techniques or descriptive analysis techniques. The end of the results of this study by showing changes in the characters contained in the novel and film Assalamualaikum Calon Imam. In the film cast there are 11 characters played in the film, 2 additional cast characters, different storyline and there is a reduction in character. This change is due to differences in the interpretation of the writer and the director. The results of the study are focused on the main characters in novels and films.